4-(Indol-3-yl)thiazole-2-amines and 4-ιndol-3-yl)thiazole Acylamines as Νovel Antimicrobial Agents: Synthesis, In Silico and In Vitro Evaluation - Sergei Simakov; Victor Kartsev; Anthi Petrou; Ioannis Nicolaou; Athina Geronikaki; Marija Ivanov; Marina Kostic; Jasmina Glamočlija; Marina Soković; Despoina Talea; Ioannis S. Vizirianakis (MDPI AG, 2021)
This manuscript deals with the synthesis and computational and experimental evaluation of the antimicrobial activity of twenty-nine 4-(indol-3-yl)thiazole-2-amines and 4-ιndol-3-yl)thiazole acylamines. An evaluation of antibacterial activity against Gram (+) and Gram (−) bacteria revealed that the MIC of indole derivatives is in the range of 0.06-1.88 mg/mL, while among fourteen methylindole derivatives, only six were active, with an MIC in the range of of 0.47-1.88 mg/mL. S. aureus appeared to be the most resistant strain, while S. Typhimurium was the most sensitive. Compound 5x was the most promising, with an MIC in the range of 0.06-0.12 mg/mL, followed by 5d and 5m. An evaluation of these three compounds against resistant strains, namely MRSA P. aeruginosa and E. coli, revealed that they were more potent against MRSA than ampicillin. Furthermore, compounds 5m and 5x were superior inhibitors of biofilm formation, compared to ampicillin and streptomycin, in terms Compounds 5d, 5m, and 5x interact with streptomycin in additive manner. The antifungal activity of some compounds exceeded or was equipotent to those of the reference antifungal agents bifonazole and ketoconazole. The most potent antifungal agent was found to be compound 5g. Drug likeness scores of compounds was in a range of −0.63 to 0.29, which is moderate to good. According to docking studies, E. coli MurB inhibition is probably responsible for the antibacterial activity of compounds, whereas CYP51 inhibition was implicated in antifungal activity. Compounds appeared to be non-toxic, according to the cytotoxicity assessment in MRC-5 cells.